Investigation of Financial Performance by Non-Financial Factors of State Hospital at Semarang - Rahani Risna Ditha; Jaluanto Sunu Punjul Tyoso; Caecilia Sri Haryanti; Muchayatin Muchayatin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
Generally financial performance research based on financial tools analyzes, and were rare using other tools. This study uses a quantitative research design to systematically analyze the impact of non-financial performance, financial applications, workload, education and training, and employee workload on the financial performance of Government Hospitals. This study used a sample of 62 government hospital employees. The data were collected through surveys and structured questionnaires, which will be statistically analyzed to identify correlations and cause-and-effect relationships among variables. The predictive value obtained from the data analysis in this study was greater than 0.00-0.05, confirming the accuracy of the research model. This indicates that the effective use of financial apps helps hospitals improve their financial performance, which is its path coefficient about 0,650. It can ultimately support the achievement of set targets and financial goals. Education and training are path coefficient about 0,380 have a significant positive effect on financial performance. These findings further support the evidence that investing in employee training is crucial for improving financial performances, especially in hospitals.